(untitled) (Bangladesh Journal of Neuroscience, 2026)
Amyotrophic lateral sclerosis (ALS), a neurodegenerative disorder, is the most common type of motor neuron disease (MND). Split-hand is considered to be an early and specific clinical sign in ALS where lateral hand (thenar muscles) is more affected than medial hand (hypothenar muscles). Split-hand index (SI) is an electrophysiological measure to see split-hand and its extent which is simple and can be done in basic electrophysiological setting. It can also differentiate ALS from other mimic disorders. It can be used as a diagnostic as well as prognostic marker of ALS so that patient can undergo an early therapeutic trial.